Assessing The Legal Consequences Of Delaying The Payment Of Achievements To Creditors - Umi Yunus (Estudiante Law Journal, 2020)
The purpose of this study is to find out the legal consequences of delaying the payment of achievements to creditors after Presidential Decree No. 12 of 2020. The methods used in this study are normative research and The type of approach used is the legal approach, the conceptual approach. The technique of analyzing legal materials in this study uses descriptive methods.  The results showed thatthe legal consequences of delaying the payment of achievements to creditors after presidential decree number 12 of 2020 related to the Determination of Non-Natural Disasters spreading Corona Virus Disease 2019 as a National Disaster falls into the category of force majure which is temporary, meaning that debtors will not be legal if there is good faith by providing reasons and evidence that Covid-19 causes delayed achievement,  However, if it does not violate good faith and does not provide valid reasons/evidence then the debtor can still be legal with the provisions of the applicable legislation. There needs to be a reaffirmation of the emergency intended in Presidential Decree 12 of 2020, in the sense of adding phrases related to economic difficulties. This is necessary so that the creation of legal certainty for debtors and creditors that the emergency due to covid-19 is classified asforce majure and delay achievements can be done